Step
*
2
1
2
of Lemma
weakly-safe-extension
1. R : ℕ ⟶ ℕ ⟶ ℙ
2. n : ℕ
3. s : ℕn ⟶ ℕ
4. weakly-safe-seq(R;n;s)
5. ¬(∀p,q:ℕ.
       (homogeneous(R;n + 1;s.p@n) 
⇒ homogeneous(R;n + 1;s.q@n) 
⇒ p < q 
⇒ (¬¬homogeneous(R;n + 2;s.p@n.q@n + 1))))
6. p : ℕ
7. q : ℕ
8. homogeneous(R;n + 1;s.p@n)
9. homogeneous(R;n + 1;s.q@n)
10. p < q
11. ¬homogeneous(R;n + 2;s.p@n.q@n + 1)
12. ¬¬(weakly-safe-seq(R;n + 1;s.p@n) ∨ weakly-safe-seq(R;n + 1;s.q@n))
⊢ ¬¬(∃p:ℕ. weakly-safe-seq(R;n + 1;s.p@n))
BY
{ TACTIC:(RepeatFor 2 (ParallelLast) THEN D -1 THEN Auto) }
Latex:
Latex:
1.  R  :  \mBbbN{}  {}\mrightarrow{}  \mBbbN{}  {}\mrightarrow{}  \mBbbP{}
2.  n  :  \mBbbN{}
3.  s  :  \mBbbN{}n  {}\mrightarrow{}  \mBbbN{}
4.  weakly-safe-seq(R;n;s)
5.  \mneg{}(\mforall{}p,q:\mBbbN{}.
              (homogeneous(R;n  +  1;s.p@n)
              {}\mRightarrow{}  homogeneous(R;n  +  1;s.q@n)
              {}\mRightarrow{}  p  <  q
              {}\mRightarrow{}  (\mneg{}\mneg{}homogeneous(R;n  +  2;s.p@n.q@n  +  1))))
6.  p  :  \mBbbN{}
7.  q  :  \mBbbN{}
8.  homogeneous(R;n  +  1;s.p@n)
9.  homogeneous(R;n  +  1;s.q@n)
10.  p  <  q
11.  \mneg{}homogeneous(R;n  +  2;s.p@n.q@n  +  1)
12.  \mneg{}\mneg{}(weakly-safe-seq(R;n  +  1;s.p@n)  \mvee{}  weakly-safe-seq(R;n  +  1;s.q@n))
\mvdash{}  \mneg{}\mneg{}(\mexists{}p:\mBbbN{}.  weakly-safe-seq(R;n  +  1;s.p@n))
By
Latex:
TACTIC:(RepeatFor  2  (ParallelLast)  THEN  D  -1  THEN  Auto)
Home
Index